Analisis Karakteristik Personal Presiden Juan Manuel Santos Pada Perundingan Damai Antara Pemerintah Kolombia dengan Kelompok Pemberontak FARC Tahun 2012-2016 - Mina Astuti Diniarti; Tri Cahyo Utomo (Journal of International Relations Diponegoro, 2019)
Long-drawn conflictis a resistor for the progress of a country. Colombia has been one of the countries that affected by internal conflict for more than 50 years due to a civil war between the government and the rebel group, FARC. Over the past few years, Colombia‟s commitment to continue to improve achieving peace has stolen the world's attention. In Juan Manuel Santos leadership era, Peace Talk Agreement (PTA) policy in 2012 became the fourth attempt for government reconciliation with the FARC. At this time, the peace negotiations used different new approaches compared to previous peace efforts. This study aims to analyze the influence of Juan Manuel Santos's personal characteristics on his decision to create peace through the Peace Talk Agreement (PTA) policy. The framework theory which used in this study is the Developing Political Personality Profile approach in Political Psychology through five elements in order to understand a leader behavior. This research used a qualitative method with an explanatory type. The results show that the development of Santos personality shaped him to be someone who cares about peace.